Hubungan Faktor Sosial Demografi dengan Psychological Distress pada Penderita Hipertensi di Kota Jayapura - Asriati Asriati; Natalia Paskawati Adimuntja; Lisda Oktavia Madu Pamangin; Helen Try Juniasti; Fajrin Violita; Christin Debora Nabuasa (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
The prevalence of hypertension in Papua has increased to 22.6%. Hypertension is a chronic disease with a high global burden and is often accompanied by psychological stress that can maintain the clinical condition and quality of life of sufferers. This study aims to describe the level of psychological stress in sufferers of hypertension and identify factors associated with it. This type of study used a cross-sectional design with a population of all sufferers of hypertension aged 18 years and above at the Abepura Community Health Center in 2025. A sample of 100 respondents was taken using the Accidental Sampling technique. Data were collected using a structured questionnaire and the K10 instrument, then analyzed descriptively, the Mann-Whitney test, and the One-way ANOVA test using Stata 13. The results showed that psychological stress in the high category was experienced by 31% of respondents, with the moderate category being 24%, the mild category being 19%, and the non-stressful category being 27%. Of all the factors analyzed, income had a significant relationship with the level of psychological distress (p = 0.040), while age, gender, marital status, and other characteristics did not show significant differences (p>0.05). The level of psychological distress in hypertension sufferers is quite high and is influenced by the sufferer's income. Therefore, mental health screening is very important for hypertension services in health facilities, especially for low-unemployment groups. Further research is needed to explore the mechanisms and effective interventions to reduce psychological distress in hypertension sufferers.